(untitled) (Research, Society and Development, 2021)
The Specificity Principle consists of the fact that the training session is connected with the game needs. Therefore, training sessions must consist of improving competences and reducing limitations, developing effective and fast behaviors by the players. This way, the present study presents, as objective, to analyze a Brazilian U-15 team training session conducted under the Specificity Principle. This research consists of a documentary and audiovisual case study, the material utilized corresponds to three analyzed videos of a football training session. As results, it can be seen that Specificity Principle was present during the entire training session, through aspects such as long defense-offense attack transitions, a game model building and the communication. On that way, it is concluded that the Specificity Principle shows itself as an important tool to integrate the game components and to solve problems presented by the complex scenario in which football is present.